2017
DOI: 10.1038/s41598-017-10168-6
|View full text |Cite
|
Sign up to set email alerts
|

Farnesoid X receptor activation protects the kidney from ischemia-reperfusion damage

Abstract: Farnesoid X receptor (FXR) activation has been reported to reduce inflammation and oxidative stress. Because both inflammation and oxidative stress are critical for tissue destruction during kidney ischemia reperfusion (I/R) injury, we investigated the protective role of FXR against kidney damage induced by I/R in mice. Mice undergoing renal I/R developed the typical features of acute kidney injury (AKI): increased creatinine, albuminuria, tubular necrosis and apoptosis. Inflammatory cytokine production and ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 58 publications
4
50
1
Order By: Relevance
“…FXR is highly expressed within the kidney, and studies have demonstrated that FXR activation can mitigate renal injury. FXR activation using obeticholic acid has been shown to decrease inflammation antioxidative stress as well as tubulointerstitial fibrosis in an ischemic reperfusion model of renal injury (37). Consistently, we demonstrated the expression of FXR is decreased during chronic injury after ureteral ligation.…”
Section: Discussionsupporting
confidence: 86%
“…FXR is highly expressed within the kidney, and studies have demonstrated that FXR activation can mitigate renal injury. FXR activation using obeticholic acid has been shown to decrease inflammation antioxidative stress as well as tubulointerstitial fibrosis in an ischemic reperfusion model of renal injury (37). Consistently, we demonstrated the expression of FXR is decreased during chronic injury after ureteral ligation.…”
Section: Discussionsupporting
confidence: 86%
“…Notably, the pathological characteristics associated with chronic ER stress are strikingly similar to hepatic FXR depletion. Furthermore, several studies have demonstrated amelioration of maladaptive ER signalling via FXR agonism in the kidney (Gai et al, ; Marquardt et al, ). These observations support the notion that FXR agonism may be involved in hepatic ER stress alleviation, although a recent study indicated that FXR activation induces hepatic ER stress via targeting XBP1/IRE1α signalling (Liu et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, previous studies have revealed that intrahepatic bile acid metabolism is associated with ER stress (Chung, Kim, Lee, An, & Kwon, ), most hepatic ER stress coexists with a lowered expression of FXRs in ageing mice (Lefebvre & Staels, ), and multiple FXR agonists have been shown to protect cells from ER stress (Chung et al, ; Ozcan et al, ). FXR activation has a cytoprotective effect in the kidney, which is mediated by supressing ER stress (Gai et al, ). These findings suggest that FXR activation could reduce hepatic ER stress, and this effect may be involved in the anti‐NAFLD effect of FXR agonists.…”
Section: Introductionmentioning
confidence: 99%
“…I/R is often associated with oxidative stress, with existing evidence suggesting that oxidative stress is a paramount contributor in causing kidney damage [25]. Therefore, the effect of Farnesiferol B on oxidative stress in the kidney after I/R was evaluated.…”
Section: Farnesiferol B Reduces Oxidative Stress and Lipid Oxidativementioning
confidence: 99%